Integrating Technology-Based Public Relations to Improve Brand Identity in Islamic Boarding Schools - Maulana, Muhammad Zaki; Mannan, Ahmad Faidul; Shulhani, Rahmat; Baharun, Hasan; Supardi, Supardi (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aims to analyze how the optimization of publication media and public relations (PR) strategies contributes to enhancing perceived quality and brand association at Nurul Jadid Islamic Boarding School. Information was obtained through document analysis, in-depth interviews with public relations managers, and direct observation of institutional communication activities using a qualitative case study methodology. The findings reveal that the strategic use of electronic Word of Mouth (e-WoM), targeted sales promotions, and symbolic interaction through social media platforms significantly improve stakeholders' perceived quality of the institution. Furthermore, the brand link is successfully reinforced by PR techniques aimed at building a favourable corporate image and enhancing brand loyalty among students and the local community. The study concludes that integrated, media-based public relations strategies are instrumental in building institutional credibility and public trust. These findings highlight the importance of adopting ethically grounded, technology-integrated PR approaches and recommend the development of a symmetrical two-way communication model to sustain the positive image and long-term relevance of Islamic boarding schools in the digital era.